Electrophilic characteristics and aqueous behavior of fatty acid nitroalkenes - Grippo, Valentina (Redox Biol, 2020)
Fatty acid nitroalkenes (NO(2)-FA) are endogenously-generated products of the reaction of metabolic and inflammatory-derived nitrogen dioxide ((.)NO(2)) with unsaturated fatty acids. These species mediate signaling actions and induce adaptive responses in preclinical models of inflammatory and metabolic diseases. The nitroalkene substituent possesses an electrophilic nature, resulting in rapid and reversible reactions with biological nucleophiles such as cysteine, thus supporting post-translational modifications (PTM) of proteins having susceptible nucleophilic centers. These reactions contribute to enzyme regulation, modulation of inflammation and cell proliferation and the regulation of gene expression responses. Herein, focus is placed on the reduction-oxidation (redox) characteristics and stability of specific NO(2)-FA regioisomers having biological and clinical relevance; nitro-oleic acid (NO(2)-OA), bis-allylic nitro-linoleic acid (NO(2)-LA) and the conjugated diene-containing nitro-conjugated linoleic acid (NO(2)-cLA). Cyclic and alternating-current voltammetry and chronopotentiometry were used to the study of reduction potentials of these NO(2)-FA. R–NO(2) reduction was observed around −0.8 V (vs. Ag/AgCl/3 M KCl) and is related to relative NO(2)-FA electrophilicity. This reduction process could be utilized for the evaluation of NO(2)-FA stability in aqueous milieu, shown herein to be pH dependent. In addition, electron paramagnetic resonance (EPR) spectroscopy was used to define the stability of the nitroalkene moiety under aqueous conditions, specifically under conditions where nitric oxide ((.)NO) release could be detected. The experimental data were supported by density functional theory calculations using 6–311++G (d,p) basis set and B3LYP functional. Based on experimental and computational approaches, the relative electrophilicities of these NO(2)-FA are NO(2)-cLA >> NO(2)-LA > NO(2)-OA. Micellarization and vesiculation largely define these biophysical characteristics in aqueous, nucleophile-free conditions. At concentrations below the critical micellar concentration (CMC), monomeric NO(2)-FA predominate, while at greater concentrations a micellar phase consisting of self-assembled lipid structures predominates. The CMC, determined by dynamic light scattering in 0.1 M phosphate buffer (pH 7.4) at 25 °C, was 6.9 (NO(2)-LA) 10.6 (NO(2)-OA) and 42.3 μM (NO(2)-cLA), respectively. In aggregate, this study provides new insight into the biophysical properties of NO(2)-FA that are important for better understanding the cell signaling and pharmacological potential of this class of mediators.